VALIDASI METODE ANALISIS DAN PENURUNAN KADAR INFUS CIPROFLOKSASIN YANG DIPENGARUHI REAKSI OKSIDASI MENGGUNAKAN HPLC - Bekti Nugraheni; Nafi'ah Nafi'ah; B Anggoro (Jurnal Ilmiah Manuntung, 2016)
Validation of analysis methods is conducted on the assay of the antibiotic ciprofloxacin because it is often used in the treatment of urinary tract infections, respiratory tract infections and gastrointestinal infections. This study aimed to determine the validity of an analytical method. Development of methods used in this study were the mobile phase of methanol: aquabidest : 0.1 M phosphate buffer: acetonitrile (80: 10: 5: 5). Then the ciprofloxacin validation was performed. After the methods validation were valid, the assay of ciprofloxacin in infusion was performed to determine the decreased levels which affected by the oxidation reaction of 0, 60, 90, 150 and 180 minutes. The validation parameters in the research were selectivity, accuracy, precision, linearity, LOD and LOQ. Samples were standart ciprofloxacin used for the validation and infusion of ciprofloxacin for the assay on the sample application that was affected by the oxidation reaction. The used of HPLC met the requirements such as HPLC devices Waters e2695 Separations, SunFireTM column C18, and PDA detector and a flow rate of 1.0 mL / min. This study showed that the result was selective, stated with no emergence of peaks in the matrix. HPLC analysis methods on ciprofloxacin meet the acceptance criteria of accuracy % recovery value solution concentration of ≥10 mg / mL are 90-107%. Precision test qualifies % RSD for solution concentrations ≥10 mg / mL is <7.3%. Linearity r ≥0,997 then it can be concluded that the result was qualified. LOD value is 0.2707 µg / mL and the LOQ value is 0.9026 µg / mL. The results of the assay infusion of ciprofloxacin were found that there was a significant decrease in the levels of ciprofloxacin due to the influence of the oxidation reaction